TINGKAT KETERBACAAN WACANA PADA BUKU PAKET KURIKULUM 2013 KELAS 4 SEKOLAH DASAR MENGGUNAKAN FORMULA GRAFIK FRY - Anih, Euis; Nurhasanah, Nesa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2016)
Readability are all elements that exist in the text (including the interaction between text) that affect the success of the reader in understanding the material they read on the speed reading is optimal. Measure the readability of a discourse needs to be done by educators to the material presented on target. There are many ways to measure the readability level of discourse, one formula Fry Graph. Fry Graph formula is quite popular because the procedure is easy. Curriculum 2013, the government issued textbooks thematic. This study aims to determine the readability level of discourse using the formula Fru Graph in this thematic books, especially books Elementary School 4th grade thematic themes ?Indahnya Kebersamaan? and ?Selalu Menghemat Energi?. This study is a descriptive analysis method, namely: based on readability formulas introduced by Edward Fry, who became known as "Fry Graph". Fry suggests that the main factor affecting the readability of a discourse or book there are two things, namely the length of the short sentence and word, difficulty level is also characterized by the number of syllables that make up each word in the discourse. Based on these results take the number of discourses that were sampled were 14 themes for ?Indahnya Kebersamaan? and 10 pieces for the theme ?Selalu Berhemat Energi. The discourse is measured based on the steps of the Fry graph readability formula. The results using Fry graphs readability formula to conclude that the book theme package ?Indahnya Kebersamaan? more suitable for level 7, 8, and 9. While on the theme?Selalu Berhemat Energi? more suitable for level 1, 2, and 3.